Uji Aktivitas Antibakteri dan Organoleptik Tempe dengan Suplementasi Cacing Lumbricus rubellus - Enggar Prahesti; Andreas Binar Aji Sukmana; Agna S. Krave (Universitas Sebelas Maret, 2025)
Typhoid fever is an infectious disease of the gastrointestinal tract caused by Salmonella typhi. Typhoid fever is often found in developing countries, including Indonesia. Earthworm Lumbricus rubellus contains lumbricin, which helps cure typhoid fever. The purpose of this study was to determine the effect of the addition of L. rubellus worm powder on the acceptance rate of panelists and the effect on inhibiting the growth of S. typhi bacteria. The research was carried out by adding worm powder with concentrations of 0%, 0.5%, 1%, and 1.5% to tempeh. Furthermore, tempeh products were tested with organoleptic tests and antibacterial tests against S. typhi using the well diffusion method. Data were analyzed using SPSS with the Kruskal-Wallis test. The results of the study on the antibacterial test showed that the addition of worm powder can increase the effectiveness of antibacterial, with the highest inhibition zone at a concentration of 1.5%, reaching 13 mm. In the organoleptic test, the value of the panelists' acceptance decreased along with the increase in the concentration of worm powder. At the concentrations of 0% and 0.5%, the panelists' response was still good, but at the concentrations of 1% and 1.5%, some began to dislike it.